การพัฒนารูปแบบการพัฒนาเชาวน์อารมณ์แบบผสมผสาน - ปิยะวรรณ เลิศพานิช (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
This research study was conducted with the purposes of constructing an integrated model of emotional intelligence development and investigating the effects of this model on teenagers. The sample came from a teenage population aged between 12-18 year of age. The subjects were 28 volunteers, who were randomly assigned to a control group of 14 and an experimental group of 14. The instruments used were emotional intelligence evaluation forms. The Cronbach’s alpha coefficient was used to calculate the reliability which was found to be .81 and the two-way ANCOVA (Analysis of Covariance) and dependent t-test method were used to analyze the data. The findings of the study were as follows: 1. The developed integrated model of emotional intelligence development consisted of A) the principle of the model, developed by studying literature, documents and research studies about emotional intelligence and methods of emotional intelligence development from the concepts of psychology, religion and social approach by integrating the three concepts. B) the purpose of the integrated model of emotional intelligence development on developing emotional intelligence in five aspects: knowing one’s emotions, managing emotions, motivating oneself, recognizing emotions in others and handling relationships. C) procedures of the model containing 1) creating a supportive environment 2) preparing the sample group 3) helping the learner set clear, meaningful and manageable goals 4) implementation of activities using the integrated emotional intelligence development 5) promotion after training. D) training results using the integrated model of emotional intelligence development as evaluated by the emotional intelligence evaluation forms developed by the researcher. 2. It was found that the result of evaluated quality of the integrated model of emotional intelligence development when it was tested by teenager, 1) after the experiment, the teenagers who received training using the integrated model of emotional intelligence development had higher emotional intelligence scores than the pretest scores at the .05 level of statistical significance, 2) after the experiment, the teenagers who received training using the integrated model of emotional intelligence development had higher emotional intelligence scores than those who did not receive training at the .05 level of statistical significance.